The effect of studends' self-assessment on their listening and speaking learning autonomy : - Nguyễn, Tuyết Lan (Trường đại học Cần Thơ, 2010)
The study aims to investigate the effect of self-regulation and attitudes to autonomous learning, and to investigate studends' attitudes towards self-assessment.